Cover Image. Issue 29 (23rd September 2021) - Tortorella, Sara; Carosati, Emanuele; Sorbi, Giulia; Bocci, Giovanni; Cross, Simon; Cruciani, Gabriele; Storchi, Loriano
Abstract : The cover image is based on the Full Paper Combining machine learning and quantum mechanics yields more chemically aware molecular descriptors for medicinal chemistry applications by Sara Tortorella et al., https://doi.org/10.1002/jcc.26737 .